Green Infrastructure Intervention To Improve Waste And Water System In Urban Areas - Hadini, Muthiah Hakim; Muzakar, Farah Bulqis; Yustiningrum, Nurlina; Hall, Nicole; Li, Peicong; Ward, Freya; Dewi, Ova Candra; Sulistiani, Coriesta Dian; Flynn, Andrew (UI Scholars Hub, 2023)
The increase in waste generation and water use in urban areas may lead to local flooding that is dangerous for health if it is not appropriately managed by waste and water systems in urban infrastructure. Sponge City is a concept that utilizes Green Infrastructures (GIs) to manage waste and water systems while still maintaining open and public spaces function. This study aims to review the waste and water infrastructure systems in Depok, Indonesia which are compared with Gainesville in the United States, America and Cardiff, United Kingdom, to give recommendations for preventing flooding in urban areas. Analysis is done by comparison of data based on factors that affect GI implementation, such as (1) management system, (2) policy context, and (3) key organizations or stakeholders. Data collected are digital statistics of the current flooding disasters, water management systems, and waste management systems are collected using web scraping of the latest news and information regarding the said topics. This study concluded three possible GI implementations in a hierarchy. The GI implementation in Depok focuses on the making of programs and management systems which involve citizen participation that prioritize the development of biopores at the household level. Gainesville focuses on Gainesville Department of Public Works which controls both waste and water management, namely through the prioritization of single-use plastic bans throughout Gainesville. In Cardiff, it focuses on the attempt of the Wales Government and Cardiff Council to make an integrated development strategy that prioritizes holistic surface water management combined with a waste disposal system. This study can open possibilities of GI implementations that reflect the urban areas characteristic in preventing local flooding by managing waste and water systems.